A study of domestic violence towards women - Isa, Khairunesa; Md Zahari, Azura; Palpanadan, Sarala @ Thulasi (Hampstead Psychological Associates, 2020)
Cases of domestic violence towards women are alarmingly increasing from year to year and attention should be seriously undertaken by all parties. This current situation of domestic violence is a reality that is occurring in our community that may influence the family institution. In general, domestic violence can be categorized as a form of abuse or threatening behaviour that may have a negative impact to the victims mainly the women like serious physical injury to the extent of permanent disability and emotional disturbance in the form of trauma and mental depression that may cause the women to commit attempted suicide. Thus, this article will discuss factors that contribute to domestic violence, the effects that will be experienced by women and the various forms of support that will be required. At the end of the discussion, various proposal will be put forward mainly the formal support networking resources to enhance the existing services.